Raising Rural Productive Uses of Electricity : A Case Study of a Successful Utility-NGO Partnership in Indonesia - Finucane, James; Besnard, Juliette; Golumbeanu, Raluca (World Bank, Washington, DC, 2021)
Too often, electrification programs do not fully exploit the degree to which access to electricity can improve livelihoods. This live wire documents the lessons learned from the World Bank-funded Indonesia Rural Electrification projects in the 1990s. The projects used marketing conducted by nongovernmental organizations to increase energy sales, investment in equipment, and productive uses of electricity by rural residents. The projects were innovative in their emphasis on productive use as an explicit goal of rural electrification efforts and in their use of non-government organizations (NGOs) to achieve results that benefited both the utility and rural residents.